Low Noise Amplifier using Darlington Pair At 90nm Technology - Rashmi Singh; Rajesh Mehra (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The demand of low noise amplifier (LNA) has been rising in today’s communication system. LNA is the basic building circuit of the receiver section satellite. The design concept demonstrates the design trade off with NF, gain, power consumption. This paper reports on with analysis of wideband LNA. This paper shows the schematic of LNA by using Darlington pair amplifier. This LNA has been fabricated on 90nm CMOS process. This paper is focused on to make comparison of three stage and single stage LNA. Here, the phase mismatch between these patameters is quantitavely analyzed to study the effect on gain and noise figure (NF). In this paper, single stage LNA has shown the 23 dB measured gain, while the three stages LNA has demonstrated 29 dB measured gain. Here, LNA designed using darlington pair shows low NF of 3.3-4.8 dB, which comparable to other reported single stage LNA designs and appreciably low compared to the three stages LNA. Hence, findings from this paper suggest the use of single stage LNA designed using Darlington pair in transceiver satellite applications.